Achieving visibility in war: an analysis of women's participation in conflict and post-conflict situations since the end of the Cold War - Cronje, Jean-Marie (My University, 2010)
War has traditionally been regarded as an exclusively male activity. Throughout time, men have been the ones to wield the sword and command the battlefield. From the military campaigns of Alexander the Great to the George W. Bush led invasion of Iraq in 2003; the theatre of war has been saturated with men and masculinity. Women, however, have either been purposefully ignored or only partially acknowledged in conflict situations. As a result, the majority of written and spoken word produced on the topic of war focuses solely on the experiences and participation of men while women have been practically rendered invisible. It is this thesis’s purpose to review the literature that has been produced on the topic of women in war since the end of the Cold War from a feminist perspective. Through this approach, this thesis will attempt to not only provide a concise overview of the literature produced on the above-mentioned topic, but through this literature review, to also make the roles of both men and women in war visible. In doing so, this thesis aims to generate an understanding of the ways in which both women and men are involved in and affected by armed conflict, as well as the ways in which gender roles, the relations between men and women are changed during and as a result of conflict.